Clinical and radiological features of pituitary stalk lesions in children and adolescents - Sung Chul Yoon; Choong Ho Shin; Sei Won Yang; Seong Yong Lee (Annals of Pediatric Endocrinology & Metabolism, 2014)
PurposeThe diagnosis of pituitary stalk lesion has been based on clinical feature, radiologic assessment for its critical location and role. This study aimed to investigate clinical symptoms, endocrine disturbance, magnetic resonance imaging (MRI) findings of pituitary stalk lesions in children and adolescents and to evaluate differences between neoplastic lesions with the others.MethodsWe performed a retrospective review of patients under 18 years old with pituitary stalk lesions diagnosed at the Seoul National University Children's Hospital between 2000 and 2013, by a text search for head MRI reports by using 'pituitary stalk', 'infundibulum', and 'infundibular stalk', as keywords.ResultsFor the 76 patients, sixteen patients (21.1%) had congenital lesions, and 52 (68.4%) had neoplasms. No inflammatory lesions were found. Diabetes insipidus (DI) was the most common endocrine defect, diagnosed in 38 patients (50%). There was male predominance especially in neoplastic group. Thickened pituitary stalk was, but enhancement of lesion was not, associated with neoplasm. DI was more prevalent in neoplastic stalk lesions. Anterior pituitary dysfunction such as growth hormone and adrenocorticotropic hormone deficiencies were less prevalent in neoplastic lesions of pituitary stalk.ConclusionIn conclusion, the etiology of pituitary stalk lesions in children and adolescents is diverse and different from that in adults. Neoplastic pituitary stalk lesions can be differentiated from nonneoplastic lesions by systemic evaluation of clinical, hormonal, radiological findings.